Diagnostic Accuracy Of Acromioaxillosuprasternal Notch Index For Prediction Of Difficult Airway Taking Cormack And Lehane Grading System As Gold Standard - Sajjad, Muhammad Mohsin; Tariq, Amina; Shabbir, Muhammad; Yousaf, Sidra (Journal of Rawalpindi Medical College, 2023)
Background: General anesthesia is still needed for several surgical interventions and requires endotracheal intubation. The difficult airway is a well-known entity, and a long list of predicting scores is present, yet a high degree of diagnostic accuracy still needs to be improved. Acromioaxillosuprasternal notch index (AASI) has shown some excellent results in recent times. Objective: Its objective is to determine the diagnostic accuracy of acromioaxillosuprasternal notch index for predicting difficult airways and to take the Cormack and Lehane grading system as the gold standard. Methodology: In this study, adults of both genders aged 20 to 70 years undergoing any surgery under general anesthesia having ASA class I to IV were included. AASI score of equal or less than 0.49 was taken as difficult airway while on Cormack and Lehane grade; it was labeled as yes where grade III or IV was seen. Results: The total number of cases were 350 cases, out of which 218 (62.29%) were males, and 132 (37.71%) were females. The mean age was 40.20±12.86 years, and the mean BMI was 24.71±3.13 (table 17). There were 294 (84%) cases in ASA Class I and II and 56 (14%) in class III and IV. Difficult intubation on AASI was seen in 54 (15.43%) and 57 (16.29%) cases on Cormack and Lehane grading. The diagnostic accuracy of AASI for prediction of difficult intubating a difficult was 96.29% with sensitivity of 90.74%, specificity of 97.30%, PPV of 85.96%, NPV of 98.29% with p= 0.001. This difference was also statistically significant with all the confounding variables like age, gender, ASA class, and BMI. Conclusion: The acromioaxillosuprasternal notch index is a significant predictor for tubing a difficult airway and taking Cormack and Lehane's grading as the gold standard. This difference is considerably better regarding age, gender, BMI, and ASA class.